The Role of Organizational Ethical Culture Moderating the Influence of Leadership Style and the Effectiveness of Internal Control System Implementation on Government Employee Performance - Erny Anggrahini; Erina Sudaryati; Reyhan Dzikriansyah Sunarno (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
This research aim to investigate the influence of leadership style and the effectiveness of the control system on the performance of government employees, while considering organizational ethical culture as a moderating variable. Quantitative approach, causal associative, path analysis model to assess variable relationships. The primary objective is to discern the direct and indirect effects of independent variables (exogenous) on the dependent variable (endogenous). Data analyzed using Partial Least Squares (PLS) with SMART PLS software, including outer and inner model testing. Research finds organizational ethical culture significantly influences and moderates leadership style's influence on employee performance. Leadership style, internal control system effectiveness don't significantly influence employee performance. Organizational ethical culture doesn't moderate this influence significantly.